3 Phase Synchronous Motor Speed Control System Using PID Control - Yun Tonce Kusuma Priyanto; Amalia Rizqi Utami; Muhammad Ridho Dewanto; Dwi Surya Santaki; Dian Wulandari (Rektorat Universitas Putra Indonesia YPTK Padang, 2022)
Synchronous motor is an alternating current (AC) motor that operates with the prime mover as the initial rotation of the rotor until the rotational speed is equal to the rotational speed of the imaginary poles on the stator. In its application a 3-phase synchronous motor needs to be set in advance so that the resulting speed is stable. In this big task of Electric Motor Control, a speed experiment was carried out on a 3-phase synchronous motor using Mathlab simulation with Siemens motor specifications, namely 50 Hz, 400 V with 16kVA power and 1500 RPM rotational speed using PID control to control the speed of a 3-phase synchronous motor so that it is more stable. From the calculations that have been carried out and the PID tuning that has been carried out, the results show that the PID control can control the motor so as to produce a more stable and efficient speed in the industry